Perilaku Alami dan Tidak Alami Burung Kakatua Jambul Kuning (Cacatua sp.) di Animal Sanctuary Trust Indonesia, Jawa Barat: Natural and Stereotype Behavior of Yellow-Crested Cockatoo (Cacatua sp.) in Animal Sanctuary Trust Indonesia, West Java - Eka arismayanti; Nisa, Nisfia Rakhmatun; Alfath Fanidya; Wildan Arsyad F; Nadya Aulia Putri; Raffiudin , Rika; Kanthi Arum Widayati (Departemen Biologi, Institut Pertanian Bogor, 2021)
Cockatoo (Cacatua sp.) is one of birds that is widely distributed in Indonesia and often kept as pet, thus threatening the Cacatua population in the wild. Environmental condition may affect the behavior of Cockatoo. Some unnatural behavior may arise due to living in the captive. Different cage conditions may result in different behavior performance in Cockatoo. Research on daily behavior at animal rescue sites at ASTI Bogor has never been conducted. This study aimed to analyze natural and stereotype behavior of Cacatua sp. at animal rescue center due to foreclosure, and analyze the relationship between cage condition and environmental factors. This study used focal instantaneous sampling, using eight individuals Cacatua sp. Cacatua sp. in ASTI performed natural behavior more than unnatural behavior, therefore ASTI can be a good place for animal rescue. The dominant natural behaviors were Resting (Re), Preening (Pr), Feeding (Fe), Locomotion (Lo), and Fighting (Fg), while unnatural behaviors were play, bite, abnormal vocalization, feather picking and aggressive. There are no difference in behavior between male and female, and also behavior in the morning and afternoon (p>0.05), but cage condition had a significant effect to daily behavior of Cacatua sp. (<0.05).